A geography of the Malay Peninsula and surrounding countries, in three parts. - Skinner, Allan Maclean ([Singapore : University of Singapore Library, 1884)
The scope is confined to Malaya, Eastern Asia and Australia, to those countries, in short, with which the colony is principally concerned. It aimsat affording such information about Malaya in particular, and Eastern Asia in general.
Keywords: Southeast Asia -- Description and travel; Malay Peninsula -- Description and travel